Motivation for return to work and actual return to work among people on long-term sick leave due to pain syndrome or mental health conditions. Issue 25 (4th December 2019) - Carlsson, Lars; Lytsy, Per; Anderzén, Ingrid; Hallqvist, Johan; Wallman, Thorne; Gustavsson, Catharina
Abstract: Purpose: The purpose of this study was to investigate associations between motivation for return to work and actual return to work, or increased employability among people on long-term sick leave. Materials and methods: Data by responses to questionnaires was collected from 227 people on long-term sick leave (mean = 7.9 years) due to pain syndrome or mild to moderate mental health conditions who had participated in a vocational rehabilitation intervention. The participants' motivation for return to work was measured at baseline. At 12-month follow-up, change in the type of reimbursement between baseline and at present was assessed and used to categorise outcomes as: "decreased work and employability", "unchanged", "increased employability", and "increased work". Associations between baseline motivation and return to work outcome were analysed using logistic and multinomial regression models. Results: Motivation for return to work at baseline was associated with return to work or increased employability at 12-month follow-up in the logistic regression model adjusting for potential confounders (OR 2.44, 95% CI 1.25–4.78). Conclusions: The results suggest that motivation for return to work at baseline was associated with actual chances of return to work or increased employability in people on long-term sick leave due to pain syndrome or mild to moderate mental health conditions. Implication for rehabilitation: High motivation for return to work seems to increase the chances of actual return to work or increased employability in people on sick leave due to pain syndrome or mild to moderate mental health conditions. The potential impact of motivation for return to work is suggested to be highlighted in vocational rehabilitation. Rehabilitation professionals are recommended to recognise and take into consideration the patient's stated motivation for return to work. Rehabilitation professionals should be aware of that the patient's motivation for return to work might have an impact on the outcome of vocational rehabilitation.